2022
DOI: 10.1111/jpn.13758
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of polyphenols on laying hens' productivity and egg quality: A review

Abstract: There has been a rapid increase in the world's output of main poultry products (meat and eggs). This reflects customer desire for these high‐quality and safe products and the comparatively low price. Recently, natural feed additives, plants and products have been increasingly popular in the poultry and livestock industries to maintain and improve their health and production. Polyphenols are a type of micronutrient that is plentiful in our diet. They are phytochemicals that have health benefits, notably cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 203 publications
1
9
0
Order By: Relevance
“…As has been widely reported by Abd El-Hack et al (2022c) , MDR is a major threat to human health, the MARI in the current study ranged from 0.27 to 0.77 for the Salmonella serovars studied. These findings are consistent with those found by Zhao et al (2017) and Kim (2021) , but some researchers have found a MARI as high as 0.91 ( Siddique et al, 2021 ).…”
Section: Discussionsupporting
confidence: 71%
“…As has been widely reported by Abd El-Hack et al (2022c) , MDR is a major threat to human health, the MARI in the current study ranged from 0.27 to 0.77 for the Salmonella serovars studied. These findings are consistent with those found by Zhao et al (2017) and Kim (2021) , but some researchers have found a MARI as high as 0.91 ( Siddique et al, 2021 ).…”
Section: Discussionsupporting
confidence: 71%
“…To better understand the favorable effects of garcinol, further analysis was conducted on the gut microbiota since its interactions with the gut play a crucial role in the maintenance of the physiological function of host health ( Lynch and Hsiao, 2019 ; Abd El-Hack et al, 2023 ). Emerging evidence demonstrates that the diversity of the intestinal microbiota of chickens is largely influenced by age and diet ( Videnska et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Salem et al (2022) , there is growing pressure on the poultry business to create superior products in large quantities for consumers. Many years ago, antimicrobial feed additives were utilized as antibiotics to boost the production of meat and eggs by controlling and preventing harmful microbes throughout the digestive system ( Abd El-Hack et al, 2022b ). Antibiotic used in chicken production has become banned because of residual antibiotics in meat products ( Youssef et al, 2018 ; Jammoul and El Darra, 2019 ) and the emergence of antibiotic-resistant microbes in humans ( Chandrakar et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%